Analysis of the cultivation of social responsibility of physical education students in the context of Healthy China - Ting Li (Physical Education of Students)
Background and Study Aim. 'Healthy China’ is an important symbol of China's social development and national prosperity. As practitioners and disseminators of sports and health, physical education of students should actively play their own specialties in the process of "Healthy China" construction. This study investigates the social responsibility and cultivation of college students so as to create a good atmosphere for educational groups from the four levels of society, family, school, and itself.